Integration of Polish Equity Securities Market with Foreign Market and Economic Growth in Poland - Bukowski, Sławomir I. (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The aim of the research which is the base for this paper has been answer the question: if Polish equity securities market with foreign market influence the economic growth in Poland? Following hypothesis was formulated: integration of Polish equity securities market with foreign market influence significantly the capital market development and economic growth in Poland. In the research applied relation between the sum of the Polish portfolio investment in the equity securities abroad and foreign portfolio investment in Polish equity securities to GDP. The econometric models were implemented in the research. The results of the research indicated that increase of Polish market of equity securities with foreign market influence positively development of capital market and economic growth in Poland.